GAMBARAN KARAKTERISTIK PASIEN LIMFADENOPATIDI RUMAH SAKIT UMUM MADANI MEDAN TAHUN 2018-2019 - Dicky Chandra Tafonao; Hermon Fanotona Marunduri; Evelyn Angie; Juliana Lina; Arie Siah Putra Siahaan (PRIMER (Prima Medical Journal), 2023)
Lymphadenopathy's a disease in the form of inflammation of lymph glands caused by bacterial, viral, protozoan, rickettsia, or fungal infections. The purpose is to describe characteristics of lymphadenitis based on age, sex, gland location, and cytological diagnosis with lymphadenitis at Madani General Hospital Medan in 2018-2019. This research uses the retrospective descriptive method with a cross-sectional approach. Data were collected from medical records and then analyzed descriptively using the SPSS application. The results showed that there were 93 patients with lymphadenopathy. Patients with lymphadenopathy, mostly in adulthood, were 57 people (61.3%). Most patients with lymphadenopathy were female, 63 people (66.7%). The most common location was on the patient's right neck in 44 people (47.3%). The most common type was lymphadenitis in 53 cases (57%). Based on the relation between age characteristics and cytological diagnosis, most patients were adult patients diagnosed with lymphadenitis were 31 people. Based on the relation between sex characteristics and cytological diagnosis, the majority of patients were female with lymphadenitis, 53 people. Based on the relation between the characteristics of the location of lymph nodes and cytological diagnosis, the most common location of inflammation in the right neck of patients with lymphadenitis were 28 people.